The Inventor of Stereo - Alexander, Robert (Routledge, 2013)
This book is the definitive study of the life and works of one of Britain's most important inventors who, due to a cruel set of circumstances, has all but been overlooked by history. Alan Dower Blumlein led an extraordinary life in which his inventive output rate easily surpassed that of Edison, but whose early death during the darkest days of World War Two led to a shroud of secrecy which has covered his life and achievements ever since. His 1931 Patent for a Binaural Recording system was so revolutionary that most of his contemporaries regarded it at as more than 20 years ahead of its time. Even years after his death, the full magnitude of its detail had not been fully utilized. Among his 128 Patents are the principle electronic circuits critical to the development of the world's first electronic television system. During his short working life, Blumlein produced patent after patent breaking entirely new ground in electronic and audio engineering. During the Second World War, Alan Blumlein was deeply engaged in the very secret work of radar development and contributed enormously to the system eventually to become 'H2S'- blind bombing radar. Tragically, during an experimental H2S flight in June 1942, the Halifax bomber in which Blumlein and several colleagues were flying, crashed and all aboard were killed. He was just days short of his 39th birthday. For many years there have been rumours about a biography of Alan Blumlein, yet none has been forthcoming. This is the world's first study of a man whose achievements should rank among those of the greatest Britain has produced. This book provides detailed knowledge of every one of his patents and the process behind them, while giving an in depth study of the life and times of this quite extraordinary man.
Online resource; Title from title page (viewed April 11, 2013)
Keywords: Blumlein, Alan Dower -- 1903-1942; Blumlein, Alan Dower; Acoustical engineering -- History; Career development; Electrical engineers -- Biography -- Great Britain; Engineers -- Biography -- Great Britain; Stereophonic sound systems -- History; Stereophonic sound systems; Theaters -- Electronic sound control; Career Mobility; Blumlein, Alan Dower; 1903-1942; Acoustique appliquée; Histoire; Plan de carrière; Ingénieurs électriciens; Grande-Bretagne; Biographies; Ingénieurs; Grande-Bretagne; Biographies; Théâtres; Commande électronique du son; Acoustical engineering; Electrical engineers; Engineers; Theaters; Electronic sound control; Great Britain; Biographies; History; Biography